2021
DOI: 10.1177/21677026211018194
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Case Studies on Dissociative Amnesia

Abstract: Dissociative amnesia, defined as an inability to remember important autobiographical experiences, usually of a stressful nature, is a controversial phenomenon. We systematically reviewed 128 case studies of dissociative amnesia reported in 60 articles that appeared in peer-reviewed journals in English over the past 20 years (2000–2020). Our aim was to examine to what extent these cases met core features of dissociative amnesia. All cases were about reports of autobiographical memory loss, but the evidence offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 145 publications
(200 reference statements)
0
32
0
Order By: Relevance
“…However, as anticipated earlier, it is worth mentioning that the link between dissociative symptoms and overreporting of bizarre symptoms has been previously identified as a potential confound (Merckelbach et al, 2017). In a recent critical review of case studies on dissociative amnesia, Mangiulli et al (2021) report that the evidence of autobiographical memory loss was weak, and insufficient to establish dissociative amnesia. In fact, most of the cases examined in the study were not able to take into account other possible factors, such as ordinary forgetfulness or malingering.…”
Section: Cut Scores and Classification Accuracymentioning
confidence: 84%
“…However, as anticipated earlier, it is worth mentioning that the link between dissociative symptoms and overreporting of bizarre symptoms has been previously identified as a potential confound (Merckelbach et al, 2017). In a recent critical review of case studies on dissociative amnesia, Mangiulli et al (2021) report that the evidence of autobiographical memory loss was weak, and insufficient to establish dissociative amnesia. In fact, most of the cases examined in the study were not able to take into account other possible factors, such as ordinary forgetfulness or malingering.…”
Section: Cut Scores and Classification Accuracymentioning
confidence: 84%
“…For instance, Riesthuis et al (2021) noticed that 64.1% (n = 98/153) of people, who admitted to have malingered memory loss at least once in their everyday life, eventually struggled in retrieving the original event. Similarly, Mangiulli et al (2021b) found that among people who had claimed to pretend to suffer from memory loss, more than half (54.1%, n = 93/172) eventually reported to have had difficulties in recalling the memory for which they malingered amnesia.…”
Section: Legal Implications Following Simulated Crime-related Amnesia Claimsmentioning
confidence: 95%
“…On the other hand, several memory scholars have criticized the very construct of dissociative amnesia [ 5 ]; in particular, some authors [ 6 , 7 , 8 ] show perplexity with respect to the diagnostic process of many cases described in the literature and believe that most of them are ambiguous, failing to definitely rule out plausible alternative explanations, such as everyday forgetfulness emerging after a trauma, ordinary forgetting and encoding failure, organic causes or malingering, or simply not thinking about something for a long time [ 6 ]. Moreover, pure dissociative amnesia should refer to a condition in which traumatic memories are stored but temporarily inaccessible, due to a dissociative coping mechanism, but there is still no clear evidence on whether the memory of a trauma can be stored and rendered inaccessible as a result of trauma itself [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, although exposure to distress should be considered a necessary trigger for the onset of memory disorder, a direct and universal connection between psychic distress or trauma and the amnesic symptomatology has not always been described in the cases presented in the literature; therefore, some authors prefer the term “pure retrograde amnesia” without psychogenic triggers [ 10 ]. Finally, even though the amnesic onset is defined as sudden, especially in localized dissociative amnesia cases, the temporal relationship with the reported traumatic/stressful triggers is not clear as symptoms have been reported to present after hours, days, or much longer after the traumatic o stressful event [ 7 ]. Thus, despite being an accepted DSM-V diagnosis, there is an ongoing debate among the scientific community surrounding the idea of dissociative amnesia so that nowadays, many regards it as a controversial memory phenomenon [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation